Dendrimer-based micelles as cyto-compatible nanocarriers. (11th July 2019) - Parshad, Badri; Yadav, Preeti; Kerkhoff, Yannic; Mittal, Ayushi; Achazi, Katharina; Haag, Rainer; Sharma, Sunil K.
Abstract : The aim of the present study is to compare the synthesized dendritic architectures in terms of self-assembly and transport potential for hydrophobic guest molecules. Abstract : A series of dendritic architectures have been synthesized using biocompatible materials such as glycerol, glucose, phloroglucinol, and alkyl chains of various sizes to give them aqueous solubility and to attain proper hydrophilic–hydrophobic balance, allowing them to form nano-sized aggregates for the encapsulation and delivery of drugs/dyes for biomedical applications. The aggregation behavior of these dendritic architectures, as well as their cytotoxicity and their cellular uptake, was studied using fluorescence measurements, dynamic light scattering (DLS), transmission electron microscopy (TEM), live cell imaging by confocal laser scanning microscopy (cLSM), and flow cytometry. The aggregation study has shown that the dendrimers proficiently self-assemble in aqueous solution with low micromolar concentration and form uniformly spread micellar aggregates. The effective cellular uptake of Nile red loaded into the dendrimers, as well as the very low toxicity of the dendrimers, indicates their potential as carriers for drugs and imaging agents.